Diagnosing Numerical Weather Prediction Forecast Errors Using Geo-Kompsat-2A Observed and Simulated Water–Vapor Imagery Within A Potential-Vorticity Dynamical Framework - Jun-Hyung Heo; Boram Kim; Minsang Kim; In-Chul Shin; Eun-Ha Sohn; KiRyong Kang (Asia-Pacific Journal of Atmospheric Sciences, 2026)
This study presents an integrated framework combining water vapor (WV) imagery, simulated water vapor (SWV), and potential vorticity (PV) diagnostics to systematically identify errors in numerical weather prediction (NWP). The analysis employs a radiance-space comparison among Geo-Kompsat-2A (GK2A) WV observations, model-simulated WV fields, and dynamically coherent PV structures. Model-equivalent WV images were generated from outputs of the Korean Integrated Model (KIM) using the Radiative Transfer for TOVS (RTTOV) model under all-sky conditions. Phase-displacement vectors and phase-corrected brightness-temperature difference fields were derived using a variational echo-tracking technique built upon the McGill Algorithm for Precipitation Nowcasting by Lagrangian Extrapolation (MAPLE). PV fields derived from KIM were composited with WV imagery to establish a dynamically consistent reference framework linking upper-tropospheric moisture structures with tropopause-level flow features. Quantitative validation over East Asia during a 1-year period (January 2025–January 2026) showed systematic reductions in root-mean-square error (RMSE) and increases in spatial correlation after phase correction across all WV channels and forecast lead times, confirming the reliability of the displacement vectors. The framework was further evaluated through two midlatitude weather events representing different manifestations of upper-level dynamical development, demonstrating its capability to diagnose forecast-error characteristics using physically consistent WV–PV–SWV relationships.

Childhood exposure to traffic-related air pollution and lung function at age 10 years: evidence of nutritional modification in a birth cohort - Yujin Park; Dong-Wook Lee; Choong Ho Shin; Young Ah Lee; Yun Jeong Lee; Dong In Suh; Yun-Chul Hong; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Soontae Kim; Kyoung-Nam Kim (International Journal of Hygiene and Environmental Health, 2026)

Deep Learning-Based Prediction of Ship Roll Motion with Monte Carlo Dropout - Gi-yong Kim; Chaeog Lim; Sang-jin Oh; In-hyuk Nam; Yu-mi Lee; Sung-chul Shin (Journal of Marine Science and Engineering, 2025)
Accurate prediction of ship roll motion is essential for safe and autonomous navigation. This study presents a deep learning framework that estimates both roll motion and epistemic uncertainty using Monte Carlo (MC) Dropout. Two architectures, a Long Short-Term Memory (LSTM) network and a Transformer encoder, were trained on HydroD–Wasim simulations covering various sea states, speeds, and damage conditions, and validated with real voyage data from two ferries, showing complementary performance, where LSTM achieved higher accuracy and Transformer provided more reliable confidence intervals. Model performance was evaluated by mean squared error (MSE), prediction interval coverage probability (PICP), and prediction interval normalized average width (PINAW). The LSTM achieved lower MSE, showing superior deterministic accuracy, while the Transformer produced higher PICP and wider PINAW, indicating more reliable uncertainty estimation. Results confirm that MC Dropout effectively quantifies epistemic uncertainty, improving the reliability of deep learning–based ship motion forecasting for intelligent maritime operations.

Ubiquitin-Specific Protease 20 Promotes CCCP-Induced Mitophagy Through Deubiquitination and Stabilization of Serine/Threonine Protein Kinase PINK1 - Ga Hyun Park; Hye In Park; Donghyuk Shin; Kwang Chul Chung (Journal of Molecular Neuroscience, 2025)

Development and validation of a portable TDLAS system for gas chromatography–level quantification of methane emissions from rice - Sujeevan Rajendran; Wonbok Lee; Sun Hwa Lee; Dongjin Shin; Da Hee Jung; Yu Mi Kang; Seok-in Yun; Byoung Il Je; Chul Min Kim; Young Hun Song (Plant Biotechnology Reports, 2025)
Rice cultivation is a significant source of agricultural methane (CH₄), yet routine quantification still relies heavily on gas chromatography (GC), which limits throughput and field deployment. Here, we evaluated a portable tunable-diode-laser absorption spectroscopy (TDLAS) detector (PMD) as an alternative to GC for measuring CH₄ released from pot-grown rice plants under field conditions. Weekly closed-chamber samples from five cultivars were analyzed in parallel by GC (FID/MS) and the PMD. Standard gas tests showed an excellent linear relationship for the PMD (R 2 = 0.9995), indicating a near-ideal response. Across field samples, GC and PMD were strongly associated (R 2 = 0.9943). Bland–Altman analysis revealed a mean bias (GC − PMD) of 8.55 with 95% limits of agreement − 9.16 to 26.26, and Lin’s concordance correlation coefficient was 0.991, evidencing near-perfect agreement despite a slight systematic offset. A simple calibration with a linear regression eliminated the bias and narrowed the limits of agreement, while preserving the high correlation. Residual analyses suggested a modest influence of CO₂ (but not N₂O) on between-method differences. Taken together, the PMD provides rapid, robust, and labor-efficient CH₄ measurements that closely match GC when a fixed calibration is applied, enabling high-throughput phenotyping of rice genotypes and management practices in both laboratory and field settings. This calibrated, portable approach lowers barriers to large-scale screening for low-emission rice, supporting climate-smart crop improvement.

Compact and cost-effective autofluorescence sensor for real-time environmental biofilm monitoring - In Ho Kim; Jae Hak Shin; Sang Bin Jeong; Gi Byoung Hwang; Chul Woo Park; Jae Hee Jung (Environmental Research, 2025)

Molecular analysis of insecticide resistance mutation frequencies in five cockroach species from Korea - Hyun Kyu Shin; Susie Cho; Gang Chan Lee; Do Eun Lee; Heung Chul Kim; In Yong Lee; Chung Hyun Ko; Soon-il Kim; Seong Soo Kim; Ju Hyeon Kim; Si Hyeock Lee (Pesticide Biochemistry and Physiology, 2025)

Particulate matter-mediated oxidative stress induces airway inflammation and pulmonary dysfunction through TXNIP/NF-κB and modulation of the SIRT1-mediated p53 and TGF-β/Smad3 pathways in mice - Ji-Hye Ha; Ba-Wool Lee; Da-Hye Yi; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Hyeon-Young Kim; Sung-Hwan Kim; In-Sik Shin; Jong-Choon Kim; In-Chul Lee (Food and Chemical Toxicology, 2024)

Cycling of phosphorus from wastewater to fertilizer using wood ash after energy production - Jae-In Lee; Chuluuntsetseg Jadamba; Soo-Cheul Yoo; Chang-Gu Lee; Myung-Chul Shin; Jechan Lee; Seong-Jik Park (Chemosphere, 2023)

Effects of melamine and cyanuric acid on placental and fetal development in rats - Woong-Il Kim; So-Won Pak; Se-Jin Lee; Changjong Moon; In-Sik Shin; In-Chul Lee; Jong-Choon Kim (Food and Chemical Toxicology, 2023)

Repositioning of the antipsychotic drug TFP for sepsis treatment - Jung Hwa Park; Hyun Jin Park; Sung Eun Lee; Young Seob Kim; Gun-Young Jang; Hee Dong Han; In Duk Jung; Kyung Chul Shin; Young Min Bae; Tae Heung Kang; Yeong-Min Park (Journal of Molecular Medicine, 2019)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Ssanghwa-Tang, a traditional herbal formula, suppresses cigarette smoke-induced airway inflammation via inhibition of MMP-9 and Erk signaling - Je-Won Ko; Na-Rae Shin; Sung-Hyeuk Park; In-Chul Lee; Jung-Min Ryu; Young-Kwon Cho; Jong-Choon Kim; Chang-Seob Seo; In-Sik Shin (Molecular & Cellular Toxicology, 2017)

Mechanism of protection by diallyl disulfide against cyclophosphamide-induced spermatotoxicity and oxidative stress in rats - Sung-Hwan Kim; In-Chul Lee; Je-Won Ko; In-Sik Shin; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Development of novel tetra- and trinucleotide microsatellite markers for giant grouper Epinephelus lanceolatus using 454 pyrosequencing - Keun-Sik Kim; Choong Hwan Noh; Shin-Joo Moon; Seung-Hee Han; In-Chul Bang (Molecular Biology Reports, 2016)

Protective effects of garlic oil against 1,3-dichloro-2-propanol-induced hepatotoxicity: role of CYP2E1 and MAPKs - Je-Won Ko; Sung-Hyeuk Park; In-Chul Lee; Sang-Min Lee; In-Sik Shin; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Extracellular calcium-binding peptide-modified ceramics stimulate regeneration of calvarial bone defects - Ju Ang Kim; Young-Ae Choi; Hui-Suk Yun; Yong Chul Bae; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2016)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Silver nanoparticles induce apoptotic cell death in cultured cerebral cortical neurons - Sung-Hwan Kim; Je-Won Ko; Suk-Kyu Koh; In-Chul Lee; Jung-Mo Son; Changjong Moon; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Perverted Head Impulse Test in Cerebellar Ataxia - Seong-Hae Jeong; Ji-Soo Kim; In Chul Baek; Jong Wook Shin; Hyunjin Jo; Ae Young Lee; Jae-Moon Kim (The Cerebellum, 2013)

Pycnogenol® prevents hexavalent chromium-induced spermatotoxicity in rats - Sung-Hwan Kim; In-Chul Lee; Hyung-Seon Baek; Changjong Moon; Seong-Soo Kang; Chun-Sik Bae; Sung-Ho Kim; Dong-Ho Shin; Jong-Choon Kim (Molecular & Cellular Toxicology, 2012)

Genomic characterization of a cell-culture-adapted Korean human G9P[8] rotavirus, CAU05-202 - Jong Wook Shin; Van Phan Le; Van Thai Than; Inseok Lim; Yoosik Yoon; Kijeong Kim; Sang-In Chung; Soon Chul Myung; Wonyong Kim (Archives of Virology, 2012)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

H89, an inhibitor of PKA and MSK, inhibits cyclic-AMP response element binding protein-mediated MAPK phosphatase-1 induction by lipopolysaccharide - Il Je Cho; Na Ri Woo; In Chul Shin; Sang Geon Kim (Inflammation Research, 2009)

Differential expression of two glutamate transporters, GLAST and GLT-1, in an experimental rat model of glaucoma - Chan Kee Park; Jiook Cha; Soo Chul Park; Phil Young Lee; Jie Hyun Kim; Hwa Sun Kim; Shin Ae Kim; In-Beom Kim; Myung-Hoon Chun (Experimental Brain Research, 2009)

Sulindac induces apoptotic cell death in susceptible human breast cancer cells through, at least in part, inhibition of IKKβ - A-Mi Seo; Seung-Woo Hong; Jae-Sik Shin; In-Chul Park; Nam-Joo Hong; Dae-Jin Kim; Won-Keun Lee; Wang-Jae Lee; Dong-Hoon Jin; Myeong-Sok Lee (Apoptosis, 2009)

Pyridoxal phosphate inhibits the group I intron splicing - Chul Jung; Sook Shin; In Kook Park (Molecular and Cellular Biochemistry, 2005)

Synthesis of kyotorphin precursor from eutectic mixtures catalysed by α-chymotrypsin - Chulyoung Kim; In Kyu Lee; Jung Eun Ahn; Chul Soo Shin (Biotechnology Letters, 2001)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

Embryo lethality and teratogenicity of a new fluoroquinolone antibacterial DW-116 in rats - Jong-Choon Kim; Hyo-In Yun; Ho-Chul Shin; Sang-Seop Han; Moon-Koo Chung (Archives of Toxicology, 2000)

Characterization of PPO (polyphenol oxidase) cDNA in sweet persimmon (Diospyros kaki) - Sung Chul Bahn; Young Soo Chung; Jeong Sheop Shin; Chang Hoo Lee; Nam In Hyung (Journal of Plant Biology, 1999)